The World after Covid-19. The New Phase of Italian Third Sector Evolution. - Bianchi, Michele (Italian Sociological Review, 2024)
Italy has witnessed some of the most tremendous consequences of Covid-19; the society has reacted to the pandemic to survive and recover. The Italian Third Sector (TS) has been constantly on the front line of the emergency putting in place services, initiatives and projects to assist those more in need. This research began with the scope to collect information about the reactions of TS organizations during the pandemic; through interviews with managers, workers and volunteers, the data collection has grasped information about the immediate responses; nevertheless, data has generated broader considerations. Through the Grounded Theory approach, this work proposes the theorization of a new step of TS in its evolution, a further affirmation of the TS as the key player that designs and manages local processes for welfare, civic empowerment and the common good. TS is now ready to lead local processes of welfare claiming for real partnerships with public actors.